Exploring teacher perceptions, commitment, and beliefs in STEM education: a systematic literature review analysis - Talib, Sariati; Alias, Bity Salwana; Matore, Mohd Effendi Ewan Mohd (International Journal of Evaluation and Research in Education (IJERE), 2025)
In recent times, science, technology, engineering and mathematics (STEM) education has gained interest in preparing students to face the challenges of the modern world. STEM fields are important for nurturing and shaping a wide range of skills in society. Therefore, to ensure students acquire the necessary skills and knowledge, STEM education has become a priority in education systems around the world, with teachers playing an important role in ensuring the success of STEM education. Therefore, teachers’ perceptions, commitments and beliefs need to be explored to gain understanding, needs and challenges for teachers to implement STEM education. This study analyzed past research findings through the systematic literature review (SLR) method with the findings of 28 articles. The findings of this past study reveal the challenges, and opportunities faced by educators through their perceptions, commitments, and beliefs in STEM education for the actions of policymakers and school leaders.